Pengelolaan Limbah Medis Padat Bahan Berbahaya dan Beracun pada Rumah Sakit Rujukan Covid-19 - Zrimurti Mappau; Miftah Chairani Hairuddin; Fajar Akbar (Jurnal Kesehatan Manarang, 2022)
Waste generated by hospital is categorized as waste containing hazardous materials (B3) which can pose a hazard to the environtment, public health and other living things if disposed of directly into environtment. The purpose of this study was to describe the management of B3 solid medical waste at the Regional General Hospital of West Sulawesi Province as the Covid-19 Patient Referral Hospital. This research is a descriptive study with an observational approach. This research was conducted at the Regional General Hospital of West Sulawesi Province which is the only Covid-19 referral hospital in Mamuju Regency. The sample of this research is the person in charge of medical waste, waste transport officers and third-party medical waste transporters as special Covid-19 patient care rooms. Data collection was carried out by direct observation in the Covid-19 patient care room. The results show that the management has been running in accordance with the SOPs issued by the Ministry of Environmental and the Director of Environmental Health including the waste sorting process is not carried out because all solid waste resulting from the activities of Covid-19 patients is classified as B3 waste. The process of transporting solid waste from the officer’s treatment room uses complete PPE. The waste treatment process is not carried out at the hospital but is handed over to a third party. The process of storing waste in a temporary storage place for B3 waste that has previously been packeged in a special container. The conclusion in this study is that the menagement of B3 solid medical waste at the West Sulawesi Provincial Hospital has been carried out in accordance with the guidlines for managing the waste of the Covid-19 referral hospital.